Motivation in tennis: a study with young tennis players - Ángela Lope Álvarez (INFAD, 2017)
One of the main factors that influence sports activity, both for its realization or execution as its continuity is the so-called motivational factor. The different objectives and goals that young tennis players have, are analyzed in this study with athletes that embrace the ages and categories from benjamin to cadets and junior. Knowing how to play well, improve a lot in this discipline along with having fun are part of the goals and goals of tennis players from ages early